Universities as agents of adaptive regional resilience: from preservation of educational and scientific schools to catalysts of territorial recovery - Byelova , Lyudmyla (Pressing Problems of Public Administration, 2025)
The main idea of this article is the conceptualization of a new role for universities that, through the preservation of academic traditions and adaptive strategies, become key institutions for restoring regional social capital. Accordingly, the article conceptualizes the new role of Ukrainian universities as agents of adaptive regional resilience under martial law conditions. The phenomenon of regional identity preservation by universities during forced displacement and digital transformation is examined through the lens of neo-institutional theory and concepts of complex adaptive systems. The vision of “adaptive regional resilience” is described, synthesizing educational institutions’ capacity to simultaneously preserve academic identity, maintain community connections, and generate innovations. Four mechanisms of identity preservation are identified: structural-institutional (“institutional translocation”), social-network (“distributed institutional presence”), cultural-symbolic (digital practices of tradition preservation), and innovation-adaptive (“crisis innovativeness”). The specificity of Kharkiv scientific schools and the scale of losses are analyzed. Three strategies for preserving scientific schools in the post-war period are proposed: “virtual collegia” (digital reincarnation of traditions through academic genealogies and mental laboratories), combination of R&D hubs with dual education and veteran requalification, and Web 3.0 validator functions (blockchain certification of competencies and scientific DAOs). It is demonstrated that Ukrainian universities exhibit the phenomenon of “dual functioning” - the ability to simultaneously preserve traditional functions and generate innovations. Five critical assumptions for strategy implementation are formulated: technological readiness, regulatory environment, financial sustainability, human capital, and geopolitical stabilization. The potential for forming the “Kharkiv phenomenon” as a new model of post-war academia recovery through integration of therapeutic functions with technological innovations is identified.